Beständigheten hos brandimpregnerat trä - Engström,Filip; Psajd,Hannes (LUTVDG/TVBB, 2024)
This report explores the properties of fire-retardant treated wood. This report has investigated the permanence for this material as well as seeing if the process of accelerated aging, which are used to determine the life span of the material, can be comparable to natural aging. The methods used for this report have been a literature and interview study in addition to practical experiments. After have being exposed to natural weather conditions for weeks, tests were made using the testing method ISO 5660-1 in the Cone Calorimeter. The results showed a notable difference between the time to ignition and the total heat release rate for the samples that had been exposed in opposition to the non-exposed. Tests were also made using infrared spectroscopy to see the chemical “fingerprint” of the material. This also showed that the amount of fire retardant in the exposed material was lower than in the unexposed material. From these results it could be determined that a difference can be noticed in the material after just a few weeks of use. It can also be concluded that more research is needed on this subject.
Keywords: Fire retardant treated wood; ISO 5660–1; Permanence; Euroclass; Cone Calorimeter; ConeTools; Infrared spectroscopy